Bước đầu khảo sát hiện tượng ý niệm hóa cảm xúc qua các động từ chuyển động /Lê Văn Thanh. - Lê, Văn Thanh.
This paper investigates the role of motion verbs in representing emotional states by means of a cross-linguistic obsrvation of English and Vietnamese, focusing on the emotion Happiness in English and nne of its equivalents, VUI SƯỚNG, in Vietnamese. The results reveals the metaphorical extension of movement constructions to conceptualize emotions in both language. It is conluded that the use of verbs encoding manner of physical movement to conceptualize a cognitive/psychological state of emotion in both languages is based on the same conceptual metaphor framework.